Actin and DNA Protect Histones from Degradation by Bacterial Proteases but Inhibit Their Antimicrobial Activity - Sol, Asaf; Skvirsky, Yaniv; Blotnick, Edna; Bachrach, Gilad; Muhlrad, Andras (Frontiers in Microbiology, 2016)
Histones are small polycationic proteins located in the cell nucleus. Together, DNA and histones are integral constituents of the nucleosomes. Upon apoptosis, necrosis and infection - induced cell death, histones are released from the cell. The extracellular histones have strong antimicrobial activity but are also cytotoxic and thought as mediators of cell death in sepsis. The antimicrobial activity of the cationic extracellular histones is inhibited by the polyanionic DNA and F-actin, which also become extracellular upon cell death. DNA and F-actin protect histones from degradation by the proteases of Pseudomonas aeruginosa and Porphyromonas gingivalis. However, though the integrity of the histones is protected, the activity of histones as antibacterial agents is lost. The inhibition of the histone's antibacterial activity and their protection from proteolysis by DNA and F-actin indicate a tight electrostatic interaction between the positively charged histones and negatively charged DNA and F-actin, which may have physiological significance in maintaining the equilibrium between the beneficial antimicrobial activity of extracellular histones and their cytotoxic effects.